2015
DOI: 10.1177/0193945915590690
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Emotional Intelligence in Predicting Postpartum Depression

Abstract: This study examines the direct and moderating effects of emotional intelligence on postpartum depression (PPD), while taking into account social support and stressful life events. Using a prospective cohort design, 165 women were surveyed in their third trimester and again at 9 weeks postpartum. Results support the direct effects of emotional intelligence (β = -.20, p = .01), social support (β = -.17, p = .04), and stressful life events (β = .17, p = .04) on PPD. Moderating effects are also supported with sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 34 publications
0
4
1
Order By: Relevance
“…With regard to the fourth hypothesis, our results indicate that depressive symptomatology is only partially associated with MSCEIT, specifically, only with the using emotions branch. These findings contrast with previous research finding an association between depression and EI ability, particularly with the branches of understanding and managing emotions (Fernández-Berrocal & Extremera, 2016; Latorre et al, 2013; Rode, 2016; Sawaya et al., 2015).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…With regard to the fourth hypothesis, our results indicate that depressive symptomatology is only partially associated with MSCEIT, specifically, only with the using emotions branch. These findings contrast with previous research finding an association between depression and EI ability, particularly with the branches of understanding and managing emotions (Fernández-Berrocal & Extremera, 2016; Latorre et al, 2013; Rode, 2016; Sawaya et al., 2015).…”
Section: Discussioncontrasting
confidence: 99%
“…The authors found that participants with depressive symptoms evaluate a neutral face in a more negative way. Rode (2016) showed that EI, measured with the MSCEIT, predicts postpartum depression in addition to social support and stressful life events. A study by Sawaya et al.…”
Section: Introductionmentioning
confidence: 99%
“…Persons with low emotional intelligence are unable to monitor their adverse emotions and are more predisposed to mental health problems (Salovey, 2001). Several studies in diverse populations (e.g., university students [Barraza‐López et al, 2017; Ordoñez, 2020; Wells et al, 2021], community adults [Salguero‐Alcaniz et al, 2021], post‐partum women [Rode, 2016]) have shown that emotional intelligence is inversely associated with depression. In addition, high levels of emotional intelligence have been suggested to protect against the occurrence of depression (Żuchowicz et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The findings of the current study are as well in agreement with what informed by Jahangard et al (2012) they showed associations between enhanced emotional intelligence and better mental health. Additionally, Rode’s (2016) study on the effects of EI on postpartum depression during the third trimester and 9 weeks after labor in 165 pregnant women has shown that EI training had a significant effect on postpartum depression. In addition, Delhom et al (2018) have reported that individuals with high EI could benefit from and use problem-solving and coping skills effectively to achieve high psychological well-being and happiness.…”
Section: Discussionmentioning
confidence: 99%